Upaya Intervensi Guru Untuk Meningkatkan Tindak Tutur Ekspresif Siswa Kelas IVB SDN 4 Tonja, Kecamatan Denpasar Utara Dalam Proses Belajar Mengajar - Ni Luh Budiasih (Jayapangus Press, 2021)
The purpose of this study was to obtain an objective description of the form of teacher intervention and the types of expressive speech acts of students in the teaching and learning process in the classroom. The theory used in this research is pragmatic theory and theory of intervention. Based on data analysis, the results of the research in cycle I are described as follows. 1) Teachers are more dominant in using preventive interventions, while psychotherapy and psychosocial use are not too often used in the learning process. 2) In the learning process, expressive speech acts were found in the form of complaints, expressing confusion, agreeing, and expressing annoyance. Students tend to convey expressive speech that expresses a sense of complaint. 3) Students 'expressive speech was born because the teacher intervened, but the effect of the intervention did not bring about positive changes in students' expressive speech. While the research results in cycle II are described as follows. 1) Teachers use preventive interventions less often, while psychotherapy and psychosocial use are more frequently used in the learning process. 2) In the learning process, expressive speech acts were found in the form of apologies, expressing requests, approving, and expressing optimism. Students seldom deliver expressive speech that expresses a sense of complaint. 3) Students 'expressive speech was born because the teacher intervened, and the effect of the intervention brought about positive changes in students' expressive speech